1998
DOI: 10.1590/s0104-14281998000400012
|View full text |Cite
|
Sign up to set email alerts
|

An Atomic Force Microscopy Study of the Interactions Involving Polymers and Silane Networks

Abstract: Silane coupling agents have been frequently used as interfacial agents in polymer composites to improve interfacial strength and resistance to fluid migration. Although the capability of these agents in improving properties and performance of composites has been reported, there are still many uncertainties regarding the processing-structure-property relationships and the mechanisms of coupling developed by silane agents. In this work, an Atomic Force Microscope (AFM) was used to measure interactions between po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this scenario, the polymer chains are being brought continuously in and out of contact with the surface. This cyclic mechanism mimics 24 Oréfice & Brennan Materials Research Figure 6. AFM tip preparation and measurements.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In this scenario, the polymer chains are being brought continuously in and out of contact with the surface. This cyclic mechanism mimics 24 Oréfice & Brennan Materials Research Figure 6. AFM tip preparation and measurements.…”
Section: Discussionmentioning
confidence: 74%
“…1. The NMR study 24 also demonstrated that the substitution occurs preferentially on the ortho position, in relation to the ether group, of benzene rings at the Bisphenol A unit ( Fig. 1).…”
Section: Chemical Modification Of Polysulfonementioning
confidence: 81%
See 2 more Smart Citations